2021 consensus statement for preventing and managing low back pain in elite and subelite adult rowers - Wilson, F.; Thornton, J. S.; Wilkie, K.; Hartvigsen, J.; Vinther, A.; Ackerman, K. E.; Caneiro, J. P.; Trease, L.; Nugent, F.; Gissane, C.; McDonnell, S.-J.; McGregor, A.; et al. (British Journal of Sports Medicine, 2021)
PURPOSE: To synthesise evidence on low back pain (LBP) in adult rowers and to create a consensus statement to inform clinical practice.